Dirty Pictures - Esra S. Padgett (Semiotic Review)
On December 17th, 2018, an adult content ban was enacted on Tumblr, a microblogging and online content-sharing platform. The ban enforced the removal of all so-called adult content through the use of a censorial algorithm designed to flag or remove images. This paper traces the discursive negotiations between Tumblr and its users that emerged after the ban, a process centered on the very terms of what defines obscenity and constituted by competing pragmatics for sorting obscene images. This article outlines the history of obscenity law in the U.S. and its use of both inherentist and performative approaches. It then traces the shift in Tumblr’s content ban, from a legal framework to an automated algorithmic agent for the task of discernment. The paper argues that disputes arising in the aftermath of the ban are the result of clashing sets of (meta)pragmatics—the semiotic processes of category-making, and image categorization more specifically—which, once the ken of juridical experts, are now brought to light by Tumblr’s act of censorship.